Analisis Energi Pada Kompresor Tiga Tingkat Yang Mengalami Penurunan Tekanan - Aloysius Eddy Liemena (ARIKA, 2010)
From the engineering thermodynamics point of view, compressor is assumed as a device of a steady-flow process that the mass of air or gas with energy as heat and work could enter or exit from the system. Air came through the compressor assumed as the ideal gas according by the first & second law of thermodynamics and had a three stage polytropic and so could calculated the steady flow worked that reversible internally. By given the mass flow rate of air, the total of power input for running the third stage compressor could be calculated. At the the three-stage compressor, the air pressure could be dropped from maximum to minimum. This research aims to decide the specific work and by obtained the air flow rate we could calculate the power input by the compressor.